Age Dynamics of Wind Risk and Tree Sway Characteristics in a Softwood Plantation - Sellier, Damien; Suzuki, Satoru (Frontiers in Forests and Global Change, 2020)
Quantifying wind risk in planted forests is critical to ensure the provision of wood-based biomaterials and forest ecosystem services in the future. Tree sway dynamics play a major role in determining their vulnerability to wind storms. While structural engineering theory can greatly assist in predicting tree and branch motion accurately, the effects of forest aging and silvicultural treatments on motion and the likelihood of mechanical failure are still poorly understood. In this study, we simulate the growth of an individual model tree and its architecture for a managed, even-aged pure Cryptomeria japonica D. Don. stand. The dynamic behavior of the tree is predicted for a rotation period at a five-year interval using finite element analysis. Results show that tree natural sway frequency is subject to a five-fold decrease over the tree’s lifetime. The tree is thus more susceptible to absorb turbulent kinetic energy from the wind as it grows older. The damping ratio, which measures how rapidly the tree can return to its rest position after being deflected, is predicted to increase by a factor of four. By simulating the mechanical response to a wind gust, the model predicts a quick transition from a low risk of failure in the juvenile phase to a high-risk situation in the mature phase. The transition occurs between ages 15 and 30 when canopy closure takes place, when juvenile wood formation stops in the lower stem region and when the first thinning is carried out. Wind risk plateaus after the transition period. The age-risk relationship shown by the model is consistent with post-typhoon damage patterns documented by inventories in Japanese planted forests, albeit with a sharper transition.